Direct contributions of dry forests to nutrition: a review - Rowland, D.; Blackie, R.R.; Powell, B.; Djoudi, H.; Vergles, E.; Vinceti, B. (Commonwealth Forestry Association, 2015)
Globally, micronutrient deficiencies are more prevalent than calorie and protein deficiencies. In order to address global micronutrient deficiencies, increasing attention is being paid to the nutritional quality of people’s diets. While conventional agriculture is key for ensuring adequate calories, dietary quality depends on the consumption of a diverse range of micronutrient rich foods. Many wild foods are rich in micronutrients, particularly fruits, vegetables, and animal source food. As a result there has been increasing interest in the value of wild foods to meeting nutritional requirements. We review literature on the consumption of wild foods in dry forest areas to assess the current state of knowledge as to how dry forests may contribute to nutrition. We focus on papers that quantify consumption of wild forest foods. Although there is a great deal of literature that lends weight to the notion that dry forests are important for food security and nutrition, we find surprisingly little evidence of direct contributions to diets. Of 2514 articles identified by our search, only four quantify the consumption of wild foods from dry forests, and only one of these puts this consumption in the context of the entire diet. There is a need for research on the nutritional importance of dry forest foods which combines methodologies from nutrition science with an understanding and appreciation of the ecological, social, cultural and economic context.